Cognitive-behavioral treatment of borderline personality disorder - Linehan, Marsha, 1943- (Diagnosis and treatment of mental disorders, 1993)
This volume is the authoritative presentation of Dialectical Behavior Therapy (DBT), Linehan's comprehensive, integrated approach to treating individuals with borderline personality disorder. DBT--which has since been adapted for other difficult-to-treat disorders involving emotion dysregulation--combines cognitive and behavioral strategies with elements of psychodynamic, strategic, and other modalities. Delineated are specific strategies for contingency management, exposure, cognitive modification, and skills training. See also Linehan's "DBT Skills Training Manual for Clinicians, Second Edition," which provides essential materials for implementing DBT skills training, plus "Client Handouts and Worksheets for DBT Skills Training, Second Edition." Also available: Linehan's instructive skills training videos for clients--"Crisis Survival Skills: Part One, Crisis Survival Skills: Part Two," "From Suffering to Freedom," "This One Moment," and "Opposite Action." Plus related DBT videos: "DBT at a Glance: An Introduction to Dialectical Behavior Therapy," "DBT at a Glance: The Role of the Psychiatrist on the DBT Team," and "Getting a New Client Connected to DBT (Complete Series)".